Anterior-Inferior Plating Results in Fewer Secondary Interventions Compared to Superior Plating for Acute Displaced Midshaft Clavicle Fractures. Issue 9 (September 2017) - Serrano, Rafael; Borade, Amrut; Mir, Hassan; Shah, Anjan; Watson, David; Infante, Anthony; Frankle, Mark A.; Mighell, Mark A.; Sagi, H. Claude; Horwitz, Daniel S.; Sanders, Roy W.
Abstract : Objectives: To determine whether a difference in plate position for fixation of acute, displaced, midshaft clavicle fractures would affect the rate of secondary intervention. Design: Retrospective Comparative Study. Setting: Two academic Level 1 Regional Trauma Centers. Patients: Five hundred ten patients treated surgically for an acutely displaced midshaft clavicle fracture between 2000 and 2013 were identified and reviewed retrospectively at a minimum of 24 months follow-up (F/U). Fractures were divided into 2 cohorts, according to plate position: Anterior-Inferior (AI) or Superior (S). Exclusion criteria included age <16 years, incomplete data records, and loss to F/U. Group analysis included demographics (age, sex, body mass index), fracture characteristics (mechanism of injury, open or closed), hand dominance, ipsilateral injuries, time between injury to surgery, time to radiographic union, length of F/U, and frequency of secondary procedures. Intervention: Patients were treated either with AI or S clavicle plating at the treating surgeon's discretion. Main Outcome Measures: Rate and reason for secondary intervention. Statistical Analysis: Fisher exact test, t test. and odds ratio were used for statistical analysis. Results: Final analysis included 252 fractures/251 patients. One hundred eighteen (47%) were in group AI; 134 (53%) were in group S. No differences in demographics, fracture characteristics, time to surgery, time to union, or length of F/U existed between groups. Seven patients/7 fractures (5.9%) in Group AI underwent a secondary surgery whereas 30 patients/30 fractures (22.3%) in group S required a secondary surgery. An additional intervention secondary to superior plate placement was highly statistically significant ( P < 0.001). Furthermore, because 80% of these subsequent interventions were a result of plate irritation with patient discomfort, the odds ratio for a second procedure was 5 times greater in those fractures treated with a superior plate. Conclusions: This comparative analysis indicates that AI plating of midshaft clavicle fractures seems to lessen clinical irritation and results in significantly fewer secondary interventions. Considering patient satisfaction and a reduced financial burden to the health care system, we recommend routine AI plate application when open reduction internal fixation of the clavicle is indicated. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.